AUTOMATIC CONTROL SYSTEM OF WINTER AUTOMOBILE-ROAD MAINTENANCE - I. I. Leonovich; I. V. Nesterovich (Наука и техника)
In order to ensure a rational usage of financial and material resources directed on winter automobile-road maintenance in theRepublicofBelarusan automatic control system of winter maintenance is under its development and introduction.  The main purpose of the system is to obtain and use meteorological information on the state of a road network that allows to take necessary organizational and technological solutions ensuring safety and continuity of traffic during winter. This system also presupposes to ensure constant control over the state of roadway covering, expenditure of anti-glazed frost materials at all levels of management.The paper considers main aspects pertaining to introduction of the automatic control system of winter maintenance